1997
DOI: 10.1677/joe.0.1540125
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of the neonatal increase in testosterone by a GnRH antagonist: the free androgen index, reproductive capacity and postmortem findings in the male marmoset monkey

Abstract: Male marmoset monkeys which had received gonadotrophin-releasing hormone (GnRH) antagonist treatment as neonates to block the postnatal increase in testosterone were studied, with the object of determining potential long-term effects of treatment on the reproductive system, including tests of fertilising capacity. To obtain information on the nature of the circulating testosterone during this neonatal period, sequential blood samples were collected from a further control group of ten neonates, aged between bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…The quiescent period was reported to continue until the age of 35 wk with non-detectable testosterone concentrations (Lunn et al 1997, Kelnar et al 2002. According to these observations, our first age group of 21 wk represented the age at which the activation of hypothalamus-pituitarygonadal axis was not expected.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The quiescent period was reported to continue until the age of 35 wk with non-detectable testosterone concentrations (Lunn et al 1997, Kelnar et al 2002. According to these observations, our first age group of 21 wk represented the age at which the activation of hypothalamus-pituitarygonadal axis was not expected.…”
Section: Discussionmentioning
confidence: 81%
“…Marmosets have been shown to have sex hormone binding globulin. Although Hodges et al (1983) reported low free testosterone levels (approximately 1.7-4.5%) in marmoset serum, Lunn et al (1997) more recently demonstrated higher levels of biologically active testosterone. Pugeat et al (1984) reported that plasma testosterone-estradiol binding protein in New World monkeys (including marmosets) has a low affinity despite high binding capacity for testosterone, resulting in high levels of unbound plasma testosterone in New World monkeys (20-40 ng/dl), as compared to those in Old World monkeys (3-9 ng/dl) or humans (10 ng/dl).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Marmosets treated neonatally with a GnRH antagonist exhibited grossly normal spermatogenesis in adulthood and are normally fertile [20]. However, comparison of individual control and treated co-twins revealed a tendency toward a decrease in germ cell volume per Sertoli cell in those GnRHa-treated co-twins in which Sertoli cell number ex-FIG.…”
Section: Discussionmentioning
confidence: 94%
“…This design enabled pair-wise comparison of data for each control and treated co-twin, thus minimizing the number of animals required for study. The primary use of the animals from which testes were obtained for the present studies (9 sets of control/GnRHa-treated co-twins; 7 other vehicle-treated controls) was for other studies [20,21] unconnected with those presented here. Starting on the day of birth, co-twins received s.c. injections of either 10 mg/kg GnRHa (Antide: Contraceptive development branch, Center for Population Research, National Institute of Child Health and Human Development [NICHD], Bethesda, MD) in propylene glycol:water (1:1, v:v) or with the vehicle alone (control).…”
Section: Animals and Treatmentsmentioning
confidence: 99%